Our ncert solutions for Miscellaneous Class 11 maths 1. Sets - ncert solutions - Toppers Study is the best material for English Medium students cbse board and other state boards students.

# Miscellaneous Class 11 maths 1. Sets - ncert solutions - Toppers Study

Topper Study classes prepares ncert solutions on practical base problems and comes out with the best result that helps the students and teachers as well as tutors and so many ecademic coaching classes that they need in practical life. Our ncert solutions for Miscellaneous Class 11 maths 1. Sets - ncert solutions - Toppers Study is the best material for English Medium students cbse board and other state boards students.

## Miscellaneous Class 11 maths 1. Sets - ncert solutions - Toppers Study

CBSE board students who preparing for **class 11 ncert solutions maths and Mathematics** solved exercise **chapter 1. Sets** available and this helps in upcoming exams
2024-2025.

### You can Find Mathematics solution Class 11 Chapter 1. Sets

- All Chapter review quick revision notes for chapter 1. Sets Class 11
- NCERT Solutions And Textual questions Answers Class 11 Mathematics
- Extra NCERT Book questions Answers Class 11 Mathematics
- Importatnt key points with additional Assignment and questions bank solved.

NCERT Solutions do not only help you to cover your syllabus but also will give to textual support in exams 2024-2025 to complete **exercise maths class 11 chapter 1** in english medium. So revise and practice these all cbse study materials like class 11 maths chapter in english ncert book. Also ensure to repractice all syllabus within time or before board exams for ncert class 11 maths ex in english.

See all solutions for class 11 maths chapter 1 exercise 1 in english medium solved questions with answers.

### Miscellaneous class 11 Mathematics Chapter 1. Sets

Sure! The following topics will be covered in this article

- Miscellaneous Class 11 Maths 1. Sets - Ncert Solutions - Toppers Study
- Class 11 Ncert Solutions
- Solution Chapter 1. Sets Class 11
- Solutions Class 11
- Chapter 1. Sets Miscellaneous Class 11

**Notice**: Undefined offset: 5 in

**/home/atpeduca/public_html/toppersstudy.com/view-home.php**on line

**123**

## 1. Sets

### | Miscellaneous |

## Miscellaneous Class 11 maths 1. Sets - ncert solutions - Toppers Study

**Miscellaneous Exercise on Chapter 1 **

**Q1. Decide, among the following sets, which sets are subsets of one and another:**

A = { x : x ∈ R and x satisfy x^{2} – 8x + 12 = 0 },

B = { 2, 4, 6 }, C = { 2, 4, 6, 8, . . . }, D = { 6 }.

**Solution: **

x^{2} - 8x + 12 = 0

x^{2} - 6x - 2x + 12 = 0

x(x - 6) -2 (x - 6) = 0

x - 6 = 0, x - 2 = 0;

x = 6 , x = 2

A = {2, 6} , B = { 2, 4, 6 }, C = { 2, 4, 6, 8, . . . }, D = { 6 }.

Every element of A is in B and C

∴ A ⊂ B, A ⊂ C,

Every Element of B is in C

∴ B ⊂ C ,

Every Element of D is in A, B and C

∴ D ⊂ A, D ⊂ B, D ⊂ C

**Q2. In each of the following, determine whether the statement is true or false. If it is true, prove it. If it is false, give an example.**

**(i) If x ∈ A and A ∈ B , then x ∈ B**

**Solution: **

False, Let be A = {1}, and B = {{1}, 2}

then 1 ∈ A and A ∈ B but 1 ∉ B

∴ x ∈ A and A ∈ B but not emply x ∉ B

**(ii) If A ⊂ B and B ∈ C , then A ∈ C**

**Solution:** False,

Let A = {1, 2} and B = {1, 2, 3, 4} and C = {{1, 2, 3, 4}, 5, 6}

According to condition,

A ⊂ B and B ∈ C but A ∉ C

A ∈ B but does not emply A ∉ C

**(iii) If A ⊂ B and B ⊂ C , then A ⊂ C**

**Solution:** True,

Let A = {a, b} , B = {a, b, c} and C = {a, b, c, d}

Here, A ⊂ B ⇒ x ∈ A and x ∈ B ------------- (i)

Similarily, B ⊂ C ⇒ x ∈ B and x ∈ C ------------------ (ii)

So, A ⊂ B and B ⊂ C ⇒ A ⊂ C

**(iv) If A ⊄ B and B ⊄ C , then A ⊄ C**

**Solution:** false;

Let A = {a, b}, B = {b, c} and C = {a, b, d, e}

Here, A ⊄ B and B ⊄ C but A ⊂ C

So, A ⊄ B and B ⊄ C do not emply A ⊄ C

**(v) If x ∈ A and A ⊄ B , then x ∈ B**

**Solution:** False;

Let A = {1,2}, B = {2, 3, 5}

1 ∈ A for all x, but 1 ∉ B

Therefore, A ⊄ B which does not imply x ∈ B.

**(vi) If A ⊂ B and x ∉ B , then x ∉ A**

**Solution:** True

A ⊂ B given

then x ∈ A and x ∈ B

While x ∉ B ⇒ x ∉ A

**Q3. Let A, B, and C be the sets such that A ∪ B = A ∪ C and A ∩ B = A ∩ C. Show that B = C.**

**Solution: **

A ∪ B = A ∪ C ..................................... (i)

A ∩ B = A ∩ C ................................................. (ii)

taking equation (i)

(A ∪ B) ∩ C = (A ∪ C) ∩ C

Using distributive law;

(A ∩ C) ∪ (B ∩ C) = C [ ∵ (A ∪ C) ∩ C = C ]

(A ∩ B) ∪ (B ∩ C) = C From equ (i) [ ∵ A ∩ B = A ∩ C ]

C = (A ∩ B) ∪ (B ∩ C) ................... (iii)

Now

(A ∪ B) ∩ B = (A ∪ C) ∩ B

using distributive law

(A ∩ B) ∪ (B ∩ B) = (A ∩ B) ∪ (C ∩ B)

(A ∩ B) ∪ B = (A ∩ B) ∪ ( B ∩ C) [∵ (B ∩ B) = B]

B = (A ∩ B) ∪ ( B ∩ C) ....................... (iv) [∵ (A ∩ B) ∪ B = B ]

From equation (iii) and (iv)

B = C proved

**Q4. Show that the following four conditions are equivalent :
(i) A ⊂ B **

**(ii) A – B = φ **

**(iii) A ∪ B = B **

**(iv) A ∩ B = A**

**Solution: **

First we try to prove

A ⊂ B ⇔ A - B = φ

**Given:** A ⊂ B

**To prove:** A - B = φ

A ⊂ B ⇒ x ∈ A and x ∈ B

then (A ∪ B) = B

(A ∪ B) ∩ B = (B ∩ B)

(A ∩ B ) ∪ (B ∩ B) = (B ∩ B)

(A ∩ B ) ∪ B = B

then (A ∩ B ) = B .................................(i)

Now also, x ∈ A ∩ B

which gives A ∩ B = A .................. (ii) [∵ A ⊂ B ]

L H S = A - B

= A - (A ∩ B ) from eqa .... (i)

= A - A using equa .. (ii)

= φ

∴ A - B = φ proved

**(ii) ⇔ (i) **

**Given :** A - B = φ

**To prove : **A ⊂ B

**Solution: **

x ∈ A - B ⇒ x ∈ A and x ∉ B

⇒ x ∈ A and x ∈ B'

⇒ A ∩ B' Here x is the element of A and B' both

∴ A ∩ B' = φ [∵ A - B = φ ] given

Again,

Let x ∈ A ⇒ x ∉ B' [∵ A ∩ B' = φ ]

There is no element that is common (A ∩ B') resulting φ.

⇒ x ∈ B

So, x ∈ A ⇒ x ∈ B

∴ A ⊂ B **Proved **

**(i) ⇔ (iii) **

Given : A ⊂ B

To prove : A ∪ B = B

**Solution: **

x ∈ A ⊂ B ⇔ x ∈ A and x ∈ B

clearly, A ∪ B = B All elements of A is in set B. [∵ A ⊂ B ]

**(i) ⇔ (iv) **

Given : A ⊂ B

To prove : A ∩ B = A

**Solution: **

x ∈ A ⊂ B ⇔ x ∈ A and x ∈ B

then x ∈ A ∩ B [∵ x is element of set A as well as set B ]

Clearly, which gives A ∩ B = A

Hence Proved

**Q5. Show that if A ⊂ B, then C – B ⊂ C – A.**

**Solution: **

Given: A ⊂ B

To show: C – B ⊂ C – A.

x ∈ C – B ⇒ x ∈ C and x ∉ B ................................... (i)

x ∈ C – A ⇒ x ∈ C and x ∉ A ................................... (ii)

while A ⊂ B

then A - B = φ

from equa. (i) and (ii)

x ∈ C – B

x ∈ C – A

∴ C – B ⊂ C – A **Proved **

**Q6. Assume that P ( A ) = P ( B ). Show that A = B**

**Solution: **

Let x is any element of set A and it is an also element of its subset say X

such that x ∈ X

then

X ⊂ A ⇒ X ∈ P(A)

⇒ X ∈ P(B) [∵ P(A) = P(B) ]

⇒ X ⊂ B

⇒ x ∈ B

x ∈ A and x ∈ B

A ⊂ B .............................. (i)

similarily,

y is any elemet of set B and it is an also element of its subset say Y such that y ∈ Y

then

Y ⊂ B ⇒ Y ∈ P(B)

⇒ Y ∈ P(A)

Y ⊂ B ⇒ y ∈ Y and y ∈ A

B ⊂ A .................................................. (ii)

From equation (i) and (ii)

A = B **Proved **

**Q7. Is it true that for any sets A and B, P (A) ∪ P (B) = P (A ∪ B)? Justify your answer. **

**Solution :** False Let A = {0, 1} and B = {1, 2}

∴ A ∪ B = {0, 1, 2}

P(A) = {Φ, {0}, {1}, {0, 1}}

P(B) = {Φ, {1}, {2}, {1, 2}}

P(A ∪ B) = {Φ, {0}, {1}, {2}, {0, 1}, {1, 2}, {0, 2}, {0, 1, 2}}

P(A) ∪ P(B) = {Φ, {0}, {1}, {0, 1}, {2}, {1, 2}}

∴ P(A) ∪ P(B) ≠ P(A ∪ B)

**Q8. Show that for any sets A and B, A = (A ∩ B) ∪ (A – B) and A ∪ (B – A) = (A ∪ B) **

**Solution : **

To show: A = (A ∩ B) ∪ (A – B)

Let x ∈ A

We have to show that x ∈ (A ∩ B) ∪ (A – B)

Case I x ∈ A ∩ B

Then, x ∈ (A ∩ B) ⊂ (A ∪ B) ∪ (A – B)

Case II x ∉ A ∩ B ⇒ x ∉ A or x ∉ B

∴ x ∉ B [x ∉ A] ∴ x ∉ A – B ⊂ (A ∪ B) ∪ (A – B)

∴ A ⊂ (A ∩ B) ∪ (A – B) … (1)

It is clear that A ∩ B ⊂ A and (A – B) ⊂ A

∴ (A ∩ B) ∪ (A – B) ⊂ A … (2)

From (1) and (2), we obtain

A = (A ∩ B) ∪ (A – B)

To prove: A ∪ (B – A) ⊂ A ∪ B

Let x ∈ A ∪ (B – A)

⇒ x ∈ A or x ∈ (B – A)

⇒ x ∈ A or (x ∈ B and x ∉ A)

⇒ (x ∈ A or x ∈ B) and (x ∈ A or x ∉ A)

⇒ x ∈ (A ∪ B)

∴ A ∪ (B – A) ⊂ (A ∪ B) … (3)

Next, we show that (A ∪ B) ⊂ A ∪ (B – A).

Let y ∈ A ∪ B ⇒ y ∈ A or y ∈ B

⇒ (y ∈ A or y ∈ B) and (y ∈ A or y ∉ A)

⇒ y ∈ A or (y ∈ B and y ∉ A)

⇒ y ∈ A ∪ (B – A)

∴ A ∪ B ⊂ A ∪ (B – A) … (4)

Hence, from (3) and (4), we obtain A ∪ (B – A) = A ∪B.

**Q9. Using properties of sets show that (i) A ∪ (A ∩ B) = A (ii) A ∩ (A ∪ B) = A. **

**Solution :** (i) To show: A ∪ (A ∩ B) = A

We know that A ⊂ A A ∩ B ⊂ A

∴ A ∪ (A ∩ B) ⊂ A … (1)

Also, A ⊂ A ∪ (A ∩ B) … (2)

∴ From (1) and (2), A ∪ (A ∩ B) = A

(ii) To show: A ∩ (A ∪ B) = A

A ∩ (A ∪ B) = (A ∩ A) ∪ (A ∩ B)

= A ∪ (A ∩ B)

**Q10. Show that A ∩ B = A ∩ C need not imply B = C. **

**Solution :** Let A = {0, 1}, B = {0, 2, 3}, and C = {0, 4, 5}

Thus, A ∩ B = {0} and A ∩ C = {0}

Now, A ∩ B = A ∩ C = {0}

However, B ≠ C [2 ∈ B and 2 ∉ C]

**Q11. Let A and B be sets. If A ∩ X = B ∩ X = Φ and A ∪ X = B ∪ X for some set X, show that A = B. (Hints A = A ∩ (A ∪ X), B = B ∩ (B ∪ X) and use distributive law)**

**Solution: **

Let A and B be two sets such that A ∩ X = B ∩ X = f

and A ∪ X = B ∪ X for some set X.

To show: A = B

Here A = A ∩ (A ∪ X) = A ∩ (B ∪ X) [A ∪ X = B ∪ X]

= (A ∩ B) ∪ (A ∩ X) [Distributive law]

= (A ∩ B) ∪ Φ [A ∩ X = Φ] = A ∩ B ….. (1)

Now, B = B ∩ (B ∪ X)

= B ∩ (A ∪ X) [A ∪ X = B ∪ X]

= (B ∩ A) ∪ (B ∩ X) [Distributive law]

= (B ∩ A) ∪ Φ [B ∩ X = Φ]

= B ∩ A = A ∩ B …… (2)

Hence, from (1) and (2), we have that A = B.

**Q12. Find sets A, B and C such that A ∩ B, B ∩ C and A ∩ C are non-empty sets and A ∩ B ∩ C = Φ. **

**Solution: **

Let A = {0, 1}, B = {1, 2}, and C = {2, 0}.

Thus, A ∩ B = {1}, B ∩ C = {2}, and A ∩ C = {0}.

∴ A ∩ B, B ∩ C, and A ∩ C are non-empty.

However, A ∩ B ∩ C = Φ

**Q13. In a survey of 600 students in a school, 150 students were found to be taking tea and 225 taking coffee, 100 were taking both tea and coffee. Find how many students were taking neither tea nor coffee?**

**Solution:**

Let U be the set of all students who took part in the survey.

Let T be the set of students taking tea.

Let C be the set of students taking coffee.

Then n(U) = 600, n(T) = 150, n(C) = 225, n(T ∩ C) = 100

To find: Number of student taking neither tea nor coffee.

Therefore, we have to find n(T' ∩ C').

n(T' ∩ C') = n(T ∪ C)'

= n(U) – n(T ∪ C)

= n(U) – [n(T) + n(C) – n(T ∩ C)]

= 600 – [150 + 225 – 100]

= 600 – 275

= 325

Hence, 325 students were taking neither tea nor coffee.

**Q14. In a group of students 100 students know Hindi, 50 know English and 25 know both. Each of the students knows either Hindi or English. How many students are there in the group?**

**Solution: **

Let U be the set of all students in the group.

Let E be the set of all students who know English.

Let H be the set of all students who know Hindi.

∴ H ∪ E = U

Then, n(H) = 100 and n(E) = 50

n( H U E ) = n(H) + n(E) – n(H ∩ E)

= 100 + 50 – 25

= 125

Hence, there are 125 students in the group.

**Q15. In a survey of 60 people, it was found that 25 people read newspaper H, 26 read newspaper T, 26 read newspaper I, 9 read both H and I,11 read both H and T, 8 read both T and I, 3 read all three newspapers. Find:**

**(i) the number of people who read at least one of the newspapers.**

**(ii) the number of people who read exactly one newspaper.**

**Solution: **

Let A be the set of people who read newspaper H.

Let B be the set of people who read newspaper T.

Let C be the set of people who read newspaper I.

Then,

n(A) = 25, n(B) = 26, n(C) = 26 , n(A ∩ C) = 9, n(A ∩ B) = 11,

n(B ∩ C) = 8 , n(A ∩ B ∩ C) = 3

Let U be the set of people who took part in the survey.

(i) n(A U B U C) = n(A) + n(B) + n(C) – n(A ∩ B) – n(B ∩ C) – n(C ∩ A) + n(A ∩ B ∩ C)

= 25 + 26 + 26 – 11 – 8 – 9 + 3 = 52

Hence, 52 people read at least one of the newspapers.

(ii) Let a be the number of people who read newspapers H and T only.

Let b denote the number of people who read newspapers I and H only.

Let c denote the number of people who read newspapers T and I only.

Let d denote the number of people who read all three newspapers.

Accordingly, d = n(A ∩ B ∩ C) = 3

Now, n(A ∩ B) = a + d

n(B ∩ C) = c + d

n(C ∩ A) = b + d

∴ a + d + c + d + b + d = 11 + 8 + 9 = 28

**Q16. In a survey it was found that 21 people liked product A, 26 liked product B and 29 liked product C. If 14 people liked products A and B, 12 people liked products C and A, 14 people liked products B and C and 8 liked all the three products. Find how many liked product C only.**

**Solution:**

Let A, B, and C be the set of people who like product A, product B, and product C respectively.

Then, n(A) = 21,

n(B) = 26,

n(C) = 29,

n(A ∩ B) = 14,

n(C ∩ A) = 12,

n(B ∩ C) = 14,

n(A ∩ B ∩ C) = 8

The Venn diagram for the given problem-

It can be seen that number of people who like product C only is

{29 – (4 + 8 + 6)} = 11

##### Other Pages of this Chapter: 1. Sets

### Select Your CBSE Classes

Important Study materials for classes 06, 07, 08,09,10, 11 and 12. Like CBSE Notes, Notes for Science, Notes for maths, Notes for Social Science, Notes for Accountancy, Notes for Economics, Notes for political Science, Noes for History, Notes For Bussiness Study, Physical Educations, Sample Papers, Test Papers, Mock Test Papers, Support Materials and Books.

*Mathematics Class - 11th*

NCERT Maths book for CBSE Students.

books

## Study Materials List:

##### Solutions ⇒ Class 11th ⇒ Mathematics

## Topper's Study

New Books